FUNGSI BADAN PENDAPATAN DAN ASET DAERAH DALAM PENGAWASAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DITINJAU DARI PERGUB NTT NOMOR 25 TAHUN 2022 TENTANG KEDUDUKAN, SUSUNAN ORGANISASI, TUGAS DAN FUNGSI SERTA TATA KERJA BADAN PENDAPATAN ASET DAERAH PROVINSI NTT - Adu, Alberto V; Yohanes, Saryono; Tupen, Rafael R (Petitum Law Journal, 2025)
The purpose of this research is to analyse the execution of the function of the Regional Revenue and Assets Agency of East Nusa Tenggara Province in overseeing Motor Vehicle Tax) revenue, as well as identifying inhibiting factors based on East Nusa Tenggara Governor Regulation Number 25 of 2022. The results showed that (1) Regional Revenue and Asset Management Agency East Nusa Tenggara Province has carried out the supervisory function through monitoring, evaluation, recommendations, and reporting, (2) but it has not been optimal due to low taxpayer awareness, the absence of standardised standard operating procedure, and limited facilities and infrastructure. Therefore, a strategy is needed to increase the effectiveness of the supervisory function and update technical policies as well as increase socialisation to the public in order to optimise revenue in the region.